Situs Gilimanuk (Bali) Sebagai Pilihan Lokasi Penguburan Pada Awal Masehi - Fadhila Arifin Aziz (Balai Arkeologi Yogyakarta, 1995)
Observations on the context of burials, in general, are a human skeleton associated with burial goods in the form of net-stamped potteries. In addition, the collection of other burial items found in the context of the tomb are beads (glass, shells, rocks), pots, cups, bowls, incense, jars, tajak, machete, eye and mouth masks, earrings, bracelets (glass, terracotta, bronze, shells), pentagonal plates, and animal remains (chickens, dogs, and pigs). All of the above burial goods are found in both childhood, adult and male and female burials.